Analisis Proses Implementasi Sistem Informasi Menuju Emr di Rumah Sakit Citra Insani Palangka Raya - Devi Delvita; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
The quality of health services is very important. This study aims to determine the analysis of the implementation of information systems towards electronic medical records at Hospital Palangka Raya. This research is a descriptive research. The research sample is 60 questionnaires. sampling method with Simple random sampling. The research was conducted from January 5 to January 25, 2023. The research instrument used a questionnaire. The research results show that the level of agreement between reality and expectations is based on predetermined variables (Man) 90.12%, Machine 85.75%, Methode) 90.06%, Material 90.18% Environment 90.94%. Based on the results of the study it is recommended to carry out regular evaluations every 6 months, repairs by providing training and collaboration with officers in improving Electronic Medical Records.